Antiinflammatory and Immunomodulating Properties of Fungal Metabolites. Issue 2 (9th June 2005) - Lull Lull, Cristina Cristina; Wichers Wichers, Harry J. Harry J.; Savelkoul Savelkoul, Huub F. J. Huub F. J.
Abstract : We discuss current information on the ability of extracts and isolated metabolites from mushrooms to modulate immune responses. This can result in a more enhanced innate and acquired disease resistance. The major immunomodulating effects of these active substances derived from mushrooms include mitogenicity and activation of immune effector cells, such as lymphocytes, macrophages, and natural killer cells, resulting in the production of cytokines, including interleukins (ILs), tumor necrosis factor alpha (TNF)-α, and interferon gamma (INF)-γ . In particular, the ability of selective mushroom extracts to modulate the differentiation capacity of CD4 + T cells to mature into T H 1 and/or T H 2 subsets will be discussed. As a consequence these extracts will have profound effects in particular diseases, like chronic autoimmune T H 1 -mediated or allergic T H 2 -mediated diseases. Immunosuppressive effects by mushroom components have also been observed. The therapeutic effects of mushrooms, such as anticancer activity, suppression of autoimmune diseases, and allergy have been associated with their immunomodulating effects. However, further studies are needed to determine the molecular mechanisms of the immunomodulating effects of mushrooms metabolites both individually and in complex mixtures, for example, extracts.